Geometric Evaluation of Stiffened Steel Plates Subjected to Transverse Loading for Naval and Offshore Applications - João Pedro T. P. de Queiroz (Journal of Marine Science and Engineering, 2019)
This work searched for the optimal geometrical configuration of simply supported stiffened plates subjected to a transverse and uniformly distributed load. From a non-stiffened reference plate, different geometrical configurations of stiffened plates, with the same volume as the reference plate, were defined through the constructal design method. Thus, applying the exhaustive search technique and using the ANSYS software, the mechanical behaviors of all the suggested stiffened plates were compared to each other to find the geometrical configuration that provided the minimum deflection in the plate’s center when subjected to this loading. The optimum geometrical configuration of stiffeners is presented at the end of this work, allowing a reduction of 98.57% for the central deflection of the stiffened plate if compared to the reference plate. Furthermore, power equations were adjusted to describe the deflections for each combination of longitudinal and transverse stiffeners as a function of the ratio between the height and the thickness of the stiffeners. Finally, a unique equation for determining the central deflections of the studied stiffened plates based only on the number of longitudinal stiffeners without significantly losing accuracy has been proposed.